Pengaruh Faktor-Faktor Risiko terhadap Kejadian Komplikasi Kehamilan di Wilayah Kerja PKM Tampa Padang - Anas, Hamdiah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Pregnancy complications remain a major cause of the increasing Maternal Mortality Rate (MMR) in Indonesia. Various risk factors, such as age, parity, pregnancy spacing, nutritional status, and maternal medical history, contribute to the incidence of these complications. Objective: This study aimed to determine the influence of risk factors on the incidence of pregnancy complications in the Tampa Padang Community Health Center (Puskesmas Tampa Padang) work area. Methods: The study used an observational analytical design with a cross-sectional approach. The study population was all 180 pregnant women in their third trimester in the Tampa Padang Community Health Center (Puskesmas Tampa Padang) work area, with a purposively selected sample of 120 respondents. Data were collected through structured questionnaire interviews and a review of the KIA (Maternal and Child Health) handbook. Data were analyzed using the Chi-Square test and multiple logistic regression. Results: A total of 32% of respondents experienced pregnancy complications, with the most common cases being preeclampsia (14%) and bleeding (10%). Bivariate analysis showed that age (p=0.012), parity (p=0.021), pregnancy spacing (p=0.034), nutritional status (p=0.018), and medical history (p=0.008) were significantly associated with the incidence of complications. Multivariate analysis showed that the most dominant factor was a history of chronic disease (OR=3.45; 95% CI=1.58–7.52). Conclusion: Maternal age, parity, pregnancy spacing, nutritional status, and medical history significantly influenced pregnancy complications, with a history of chronic disease being the dominant factor. Promotional and preventive efforts are needed through early risk detection and reproductive health education at the Tampa Padang Community Health Center.